Merger between Boeinga and McDonnell - a marriage made in heaven? - Bhat, Sangeetha (2012)
Growing the business inorganically is a very attractive option for a lot of companies. The trouble is mergers and acquisitions (M&A) are not jump starters or quick fix solutions in most cases. In 2011 alone there were M&A transactions that were in the range of USD $2.18 trillion (merger market, 2011) Looking at the sheer size of M&A deals one wonders if it is as attractive at all in reality? Based on significant M&A analysis over the last 40 years it is estimated that about 45-82% of the M&A transactions fail. ((cf. Kitching, 1967; Jensen & Ruback, 1983; Hunt, 1990; Jarrell & Poulsen, 1994; Mueller, 2003). So the obvious question is why some of the M&A deals succeed? There has not been much research around identifying the causes and failures of these big M&A deals. The biggest issue with merger transactions is the case of integration issues apart from identifying the right targets at the right price. (Christensen et al, 2011)